Sex-specific differences in biomechanics among runners: A systematic review with meta-analysis - Xie, P.-P.; Istvan, O.; Liang, M. (Frontiers in Physiology, 2022)
Patellofemoral disorders are more common in female runners compared to their male counterparts. Differences in biomechanical characteristics between groups of runners could provide insight into the causes of higher rates of injury in female versus male runners, which would be useful to physical therapists and athletic trainers in development of individualized injury prevention programs. This review compares the differences in biomechanical characteristics between female and male runners. Electronic databases, including PubMed, Scopus, Web of Science, and Embase were searched in December 2021 for studies evaluating sex-specific differences in lower limb mechanics of healthy participants during running. Two independent reviewers determined the inclusion and quality of each research paper. Meta-analyses were used where possible. A total of 13 studies were selected. Means and standard deviations of reported data were retrieved from each selected paper for comparison of results. Three biomechanical variables, including dynamics, muscle activation, and kinematics, were compared between female and male runners. However, no differences were found in kinetic variables or muscle activation between groups due to insufficient data available from the selected studies. Meta-analyses of kinematic variables revealed that female runners exhibited significantly greater hip flexion angle, hip adduction angle, and hip internal rotation angle, but smaller knee flexion angle compared to male runners during running. We found significant differences in kinematic variables between female and male runners, which could influence the training advice of physical therapists and athletic trainers who work with runners, and inform the development of injury prevention programs.